Wooden household furniture: Does brand matter? - Mohamed, Shukri; Abdullah, Suhaidi (Universiti Putra Malaysia Press, 2006)
Consumers evaluate a product based on various attributes when making a purchase decision. The attributes considered and their importance varies among individuals and differs between products. This paper reports the findings from an exploratory study on the importance of brands in wooden household furniture purchase decision among Malaysian consumers. A structured, self-administered questionnaire was used to collect data from the respondents. Results indicated that the respondents are not concerned about brands, but are instead price-conscious and placed more importance on the tangible attributes ofthe wooden household furniture items. Brand familiarity among the respondents was low. This paper discusses how the wooden household furniture manufacturers can brand their product in an effective way.